Joint Operation of a Cross member with Multi-Hollow Floor Slabs - Damirovich, Khamrokulov Ulugbek (Research Parks Publishing LLC, 2022)
The article presents the results of testing a reinforced concrete crossbar and a fragment of a ceiling with prefabricated multi-hollow slabs for a short-term load. The bearing capacity and deflections of beams are compared without and taking into account joint work with hollow-core slabs. Nowadays, when designing multi-storey frame buildings, their staged erection, and, accordingly, loading is not taken into account in the calculations. In addition, in monolithic reinforced concrete frames, the joint work of prefabricated multi-hollow reinforced concrete slabs with crossbars is not taken into account. This is explained by the fact that the experimental data on taking into account the joint operation of crossbars with multi-track slabs is not sufficient. To evaluate the joint operation of crossbars with multi-track slabs, an experimental study of the model of a prefabricated-monolithic crossbar on the auction of short-term loads was carried out.